The Doctor-Manager Relationship - Basnet Chhetri, Raju (Journal of Universal College of Medical Sciences, 2018)
Healthcare service in itself is one of the most crucial, most sensitive services in the world. Advancement in healthcare infrastructures, equipment and manpower are rapid day by day. “Healthcare service providers”, the definition is changing from commonly perceived “doctors” to “doctors plus managers”. The healthcare practice has changed all its way from individual practice to communal, organised hospital systems; resources are pooled in a common place; where patients expect for every kind of treatment once they enter the common roof. However, the hospital only can understand the role the doctor and manager play together for quality healthcare services. The two now cannot be separated despite of several disparities that appear between them.There should always be an effort to bridge the gap between them which appears between them despite serving the common goal. Doctor manager collaboration including collaboration of education system shall bring the real bond between them to understand each other, understand system and pace for their common goal. Journal of Universal College of Medical Sciences (2017) Vol.05 No.01 Issue 15, page: 49-53